A Novel Alternative to Colectomy for Severe Intractable Constipation in Adults: How to Avoid Surgery in Severe Cases? - Stammers, Matthew; Cummings, Fraser; Mills, Matilda; Coleman, Nicholas; Gwiggner, Markus (Archives of Clinical and Medical Case Reports, 2019)
We report on two cases of severe intractable constipation that underwent insertion of a percutaneous endoscopic gastrostomy (PEG) tube to facilitate home colonic irrigation, both resulting in dramatic clinical response. The first case was of a 59 year old lady who developed severe constipation following multiple failed surgical procedures. The second was a 52 year old lady with absent pelvic floor function on magnetic resonance defecating protography. Both had failed to respond to medical management, including sodium picosulphate and were being frequently admitted to hospital. As we detail in this report for both patients the PEG tube was inserted with the intention of facilitating colonic irrigation with 2-3 litres of polyethylene glycol laxative daily. One patient went from receiving 25 endoscopically-administered high sigmoid enemas per year to 0, the other patient avoided colonic de-functioning. We propose that PEG tube insertion to facilitate colonic irrigation with polyethylene glycol is a viable novel treatment option which appears to be effective and safe for the management of severe constipation in selected cases. As we detail in this paper this approach comes with several advantages over traditional approaches and appears to be associated with a lower complication rate.